Materials and Processing Technologies Selected, peer-reviewed papers from the National Conference on Mechanical Engineering and Manufacturing (NCMME 2019), October 18-20, 2019, Ho Chi Minh City, Vietnam - Nguyen, Thanh Nam (Key Engineering Materials Ser., 2020)
This volume contains papers congregated by the result of the National Conference on Mechanical Engineering and Manufacturing (NCMME 2019, 18-20 October 2019, Vietnam). The presented collection is a 1st part which describes recent developments in the area of materials science and materials machining. Steel, Aluminium, Plywood, Friction Stir Welding, Injection Molding, 3D Printing, Forming, Bending, Technological Parameters Materials Science, Mechanical Engineering, Manufacturing.